Mídia, intersubjetividade e quotidianidade: Etnografia das práticas comunicacionais em uma feira de Belém - CASTRO, Fábio Fonseca de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This article describes an ethnographic research with the support of ethnomethodology held on a market in the city of Belém, Pará in two periods: the first one with nine months in 2011-12 and the other one with six months in 2015. Observing the communicational and cultural processes present in the social interactions present in this market, we try to describe the typifications (Schutz, 1967) that conforms intersubjectivity of social subjects who attend there. Along the way, we describes and discusses these typifications as social forms (Simmel, 1999; Simmel, 2006) of a banal everyday life (Heidegger, 1976, Heidegger, 1985; Heidegger 1992) and we seek to reflect on these typifications through Heidegger's notion of iddle talk (Gerede), understood as communication and cultural process accustomed to the banality of everyday life.